Genome-wide association study identifies 16 genomic regions associated with circulating cytokines at birth - Wang, Yunpeng; Nudel, Ron; Benros, Michael E.; Skogstrand, Kristin; Fishilevich, Simon; Lancet, Doron; Sun, Jiangming; Hougaard, David M.; Andreassen, Ole A.; Mortensen, Preben Bo; Buil, Alfonso; Hansen, Thomas F.; et al. (PLoS genetics, 2020)
Circulating inflammatory markers are essential to human health and disease, and they are often dysregulated or malfunctioning in cancers as well as in cardiovascular, metabolic, immunologic and neuropsychiatric disorders. However, the genetic contribution to the physiological variation of levels of circulating inflammatory markers is largely unknown. Here we report the results of a genome-wide genetic study of blood concentration of ten cytokines, including the hitherto unexplored calcium-binding protein (S100B). The study leverages a unique sample of neonatal blood spots from 9,459 Danish subjects from the iPSYCH initiative. We estimate the SNP-heritability of marker levels as ranging from essentially zero for Erythropoietin (EPO) up to 73% for S100B. We identify and replicate 16 associated genomic regions (p < 5 x 10 −9 ), of which four are novel. We show that the associated variants map to enhancer elements, suggesting a possible transcriptional effect of genomic variants on the cytokine levels. The identification of the genetic architecture underlying the basic levels of cytokines is likely to prompt studies investigating the relationship between cytokines and complex disease. Our results also suggest that the genetic architecture of cytokines is stable from neonatal to adult life.